Systems for Arctic spill response - Schultz, L. A.; United States. Coast Guard. Office of Research and Development. (Washington : Dept. of Transportation, Coast Guard, Office of Research and Development, 1978)
Final report; March 1978. Includes bibliographical references. v. 1. [Summary] -- v. 2. Appendices. Prepared by ARCTEC, Inc., under contract Mode of access: Internet.